Dynamic changes in BDNF, VEGF, and GDNF after transplanting human protein-based scaffolds with Wharton’s Jelly MSCs in a rat brain injury model - Wioletta Lech; Marta Kot; Marlena Welniak-Kaminska; Monika Drabik; Leonora Buzanska; Marzena Zychowicz (Scientific Reports)
Abstract Stroke poses a considerable challenge for regenerative medicine due to the complex and multidimensional specificity of the central nervous system, and cell therapy is one of the currently considered treatments. The aim of this study was to determine the pro-regenerative outcome after transplantation of preconditioned and scaffold-encapsulated mesenchymal stem/stromal cells isolated from Wharton’s Jelly (WJ-MSCs) in an experimental rat model of brain injury. For this purpose, WJ-MSCs cultured at different oxygen concentrations (21% O2 or 5% O2) were transplanted into the injured rat brain in saline or hydrogel scaffolds derived from human platelet lysate or fibrinogen. Using magnetic resonance imaging, we observed the signal of labelled WJ-MSCs at injection site at different time-points after transplantation. By diffusion-weighted imaging we detected the signal at the lesion site only after WJ-MSCs transplantation. Furthermore, cell transplantation resulted in a significant decrease in the extent of brain damage and dynamic change in the expression of investigated rat trophic factors (BDNF, GDNF, VEGF-A) in the brain and cerebrospinal fluid. The highest increase in this expression was observed after transplantation of physioxia-preconditioned and scaffold-encapsulated cells. The results demonstrated the regenerative effect of WJ-MSCs, which was enhanced by their transplantation within human protein-based hydrogel scaffolds in the rat model of brain injury.